Frequency of Uterine Leiomyomas in Multipara Women: Frequency of Uterine Leiomyomas in Multipara Women - Latif, Fatima; John, Akash; Ali, Abid; Afsar, Rehan; Ashfaq, Iqra (Pakistan Journal of Health Sciences, 2022)
Fibroids are typically well-defined solid masses that have a convoluted appearance. These are generally echogenic like the myometrium, though sometimes they can indeed be hypoechoic. Objective: To determine the incidence of uterine leiomyomas in multipara women in Gujranwala, Pakistan. Methods: A cross-sectional study was conducted at the diagnostic department of radiology (DHQ/Teaching Hospital, Gujranwala). The study lasted for three months, from February 24, 2022, to May 24, 2022. A total of 140 people participated in the research after written informed consent. 140 multiparous women with uterine fibroids were included between the mentioned dates. The examination of the patients included pelvic ultrasonography with a full bladder. Results: This survey consisted of 140 multiparous women. 100 (64.1%) of 140 females having fibroid uterus who reported to the gynaecology department exhibited submucosal fibroids, 33 (21.2%) contained intramural fibroids, and 23 (14.7%) of them had subserosal fibroids. Fibroids with 127 (81.4%) in the anterior and 29 (18.6%) in the posterior were observed. Menstrual inconsistency was the most prevalent clinical presentation of reported cases, featuring menorrhagia in 105 (75%) patients, polymenorrhagia in 24 (17.1%) patients, and abdominal discomfort in 44 (31.4%) patients, and urinary frequency in 29 (27.9%) women. A total of 47 (33.6%) of the females had a family background of uterine fibroids. Conclusion: Submucosal fibroids are the most abundant, followed by intramural and subserosal fibroids, with pedunculated fibroids being the least frequent. The anterior part of the uterus is the most probable site of fibroid emergence. Menorrhagia was the most prevalent symptom.